No Relationship Between Visual Field Damage And Choroidal Thickness In Eyes With Primary Open Angle Glaucoma - Karaca, Umut; Özge, Gökhan; Mumcuoglu, Tarkan; Usta, Gulsah (Ophthalmic research, 2020)
To evaluate the association between visual field damage and choroidal thickness (ChT) in subjects with primary open angle glaucoma Methods: In this cross-sectional study, 115 eyes of 58 glaucoma patients and 112 eyes of 56 healthy subjects were enrolled. ChT at the fovea, 0.5 mm temporal, 1.5 mm temporal, 0.5 mm nasal, 1.5 mm nasal to the fovea, and all quadrants in the peripapillary region were analyzed. The subjects with glaucoma were further classified by Hodapp-Anderson-Parrish (HAP) scores. There was no difference between glaucoma and healthy subjects in mean age, gender, and refractive errors. The overall average thickness of the retinal nerve fiber layer (RNFL) was significantly lower in the eyes with glaucoma compared to the normal subjects (p<0.01) and decreased in proportion to the severity of glaucoma (normal, 99.4; no defect, 89; early, 80.4; moderate, 63.1; and severe, 51 µm). ChT measured from the foveal region, at a distance of 500 μm from the fovea (nasal and temporal), and 1500 μm from the fovea (nasal and temporal) did not significantly vary between the two groups. As well, peripapillary ChT did not significantly differ in proportion to the severity of glaucoma (p>0.05 for all quadrants). The RNFL and ChT measurements were not significantly correlated with any peripapillary location (|r|≤0.17, p>0.05). The visual field MD/PSD and ChT measurements were also not significantly correlated with any peripapillary and macular location (|r|≤0.12, p>0.05). There was no significant difference in macular and peripapillary ChT between healthy and glaucomatous eyes that differed in severity of visual field damage. This suggests that the structural features of the choroid may not be associated with severity of primary open angle glaucoma.